Hydrodeoxygenation of Castor Oil As an Alternative Source of Biohydrocarbon Using Nickel Catalyst Loaded On Hzsm-5 Zeolite - Muhammad Abimansyah Saragih; Muhammad Irvan Hasibuan; Loren Simangunsong; Ahmad Nasir Pulungan; Junifa Layla Sihombing (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2022)
Abstract: The need for energy continues to increase along with rapid population growth. Fuel is one of the most critical energy sectors. However, the limited availability of fossil fuels and the issue of air pollution have prompted various studies to find alternative fuels that are renewable and environmentally friendly. In this study, the conversion of castor oil into biohydrocarbons through the hydrodeoxygenation (HDO) process using the HZSM-5 catalyst loaded with Ni (Ni/HZSM-5) aims to produce biohydrocarbon products as a component of liquid fuel. This research has been carried out in 3 main stages, including: 1) Catalyst preparation; 2) Catalyst characterization; and 3) Activity and selectivity test of HZSM-5 catalyst and Ni/HZSM-5 in the hydrodeoxygenation process of castor oil at reaction temperatures of 350 oC, 375 oC, and 400 oC. The conversion results of castor oil using HZSM-5 and Ni/HZSM-5 catalysts were 3.23%, 25.65%, 43.72%, and 13.78%, 35.03%, 71.01%, respectively. From the GC-MS analysis data on the product at 400 oC, the selectivity of HZSM-5 and Ni/HZSM-5 was 20.02% and 23.71% for the kerosene fraction, as well as 15.79% and 11.01% for the gasoil fraction, respectively.Abstrak: Kebutuhan energi terus meningkat seiring dengan pertumbuhan jumlah penduduk yang sangat pesat. Salah satu sektor energi yang paling dibutuhkan adalah bahan bakar minyak. Namun kesediaan bahan bakar fosil yang terbatas dan isu pencemaran polusi udara, mendorong berbagai penelitian untuk menemukan alternatif bahan bakar yang terbarukan dan ramah lingkungan. Dalam penelitian ini, konversi minyak jarak menjadi biohidrokarbon melalui proses hidrodeoksigenasi (HDO) menggunakan katalis HZSM-5 teremban logam Ni (Ni/HZSM-5) bertujuan untuk menghasilkan produk biohidrokarbon sebagai komponen bahan bakar cair. Penelitian ini telah dilakukan dengan 3 tahapan utama yaitu 1) Preparasi katalis, 2) Karakterisasi katalis, 3) Uji aktivitas dan selektifitas katalis HZSM-5 serta Ni/HZSM-5 dalam proses hidrodeoksigenasi minyak biji jarak dengan temperatur proses 350 oC, 375 oC, dan 400 oC. Hasil konversi minyak biji jarak dengan menggunakan katalis HZSM-5 dan katalis Ni/HZSM-5 berturut-turut sebesar 3.23%, 25.65%, 43.72% dan 13.78%, 35.03%, 71.01%. Dari data analisis GC-MS produk di suhu 400 oC diperoleh selektivitas katalis HZSM-5 dan katalis Ni/HZSM-5 berturut-turut adalah 20.02% dan 23.71% untuk fraksi kerosene, serta 15.79% dan 11.01% untuk fraksi gasoil.